Effectiveness and Safety of Oxcarbazepine vs. Levetiracetam as Monotherapy for Infantile Focal Epilepsy: A Longitudinal Cohort Study - Zhao, Binyang; Liao, Shuang; Zhong, Xuefei; Luo, Yuanyuan; Hong, Siqi; Cheng, Min; Zhang, Jie; Li, Tingsong; Jiang, Li (Frontiers in Neurology, 2022)
Objective This study aimed to compare the effectiveness and safety of oxcarbazepine (OXC) vs. levetiracetam (LEV) for treating infantile focal epilepsy in a longitudinal cohort study. Methods We enrolled 187 consecutive patients aged 2–24 months who received OXC or LEV as initial monotherapy; 161 patients completed the study. The longitudinal analysis involved anti-seizure medication (ASM) responsiveness, safety, the establishment of epilepsy syndrome, and etiology over a median follow-up of 2 years (interquartile range [IQR] 1.6–2.4). The relative efficacy and retention rates of OXC vs. LEV were evaluated using generalized linear regression models and the Cox proportional hazards model. Results The 161 patients who completed the study had comparable baseline demographics and clinical variables between the OXC group (n = 83) and LEV group (n = 78). Overall, the mean age at onset was 6 months (IQR 4.3–9). The most common epilepsy syndrome was self-limited familial/non-familial infantile epilepsy (54.7%). Epilepsy was related to genetic and unknown causes in 34.2 and 52.2% of the patients, respectively. OXC achieved significantly higher responses than LEV for seizure freedom (risk ratio [RR] = 1.71, 95% confidence interval [CI] = 1.28–2.73, P < 0.001) and 12-month retention rate after onset (hazard ratio [HR] = 1.84, 95% CI = 1.15–2.95, P = 0.007). Moreover, OXC showed more obvious effects for patients aged < 1 year diagnosed with self-limited familial/non-familial infantile epilepsy and non-syndromic epilepsy with genetic or unknown causes. The adverse events related to both OXC and LEV were well-tolerated. Significance OXC could be an alternative to LEV for treating infantile focal epilepsy. OXC monotherapy can be considered first-line treatment for patients aged <12 months and those with epilepsy without developmental and epileptic encephalopathy.